1995
DOI: 10.1016/s0969-2126(01)00239-8
|View full text |Cite|
|
Sign up to set email alerts
|

2 å crystal structure of an extracellular fragment of human CD40 ligand

Abstract: The structure suggests that most of the hyper-IgM syndrome mutations affect the folding and stability of the molecule rather than the CD40-binding site directly. Despite the fact that the hyper-IgM syndrome mutations are dispersed in the primary sequence, a large fraction of them are clustered in space in the vicinity of a surface loop, close to the predicted CD40-binding site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
0
3

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(153 citation statements)
references
References 37 publications
(42 reference statements)
7
141
0
3
Order By: Relevance
“…It has been reported that the receptors and the ligands form a trimeric structure (Karpusas et al, 1995;Gruss, 1996;Schneider et al, 1997;Hymowitz et al, 1999). Interestingly the ligands are expressed as transmembrane proteins but soluble forms have been identified for all of them (Schneider and Tschopp, 2000).…”
Section: Death Receptor Proteinsmentioning
confidence: 99%
“…It has been reported that the receptors and the ligands form a trimeric structure (Karpusas et al, 1995;Gruss, 1996;Schneider et al, 1997;Hymowitz et al, 1999). Interestingly the ligands are expressed as transmembrane proteins but soluble forms have been identified for all of them (Schneider and Tschopp, 2000).…”
Section: Death Receptor Proteinsmentioning
confidence: 99%
“…In the CD40L.G 4 S.A vector, CD40L is linked to the 4070A-SU via a non-cleavable AAAG 4 S linker, and in CD40L.MMP.A, via a MMP-cleavable linker (AAAPLGLWA). The SfiI-NotI PCR fragment encoding the 146 amino acids of the soluble extracellular domain of the trimeric CD40L (Gly 116-Leu 261) 30 was generated using a CD40L cDNA template (ATCC 79813; Rockland, MD, USA) and two primers (with restriction sites underlined), sCD40Lb (5Ј Ͼ CCG GTA CCG GCC CAG CCG GCC GGT GAT CAG AAT CCT CAA ATT GC) with a SfiI site and nCD40Lf (5Ј Ͼ AAG TCT TAG CGG CCG CGA GTT TGA GTA AGC CAA AGG) with a NotI site. To obtain CD40L.G 4 S.A and CD40L.MMP.A, the SfiI-NotI digested CD40L PCR fragment was cloned into SfiI-NotI digested E.G 4 S.A or E.MMP.A backbones, respectively.…”
Section: Construction Of Chimeric Envelope Expression Vectorsmentioning
confidence: 99%
“…We have generated a three-dimensional structure of CD40L and CD40 using the X-ray structure of the receptor binding extracellular portion of CD40L (Karpusas et al, 1995), together with a model of CD40 based upon the modular approach of Naismith and Sprang (1998; hence called Model 2). Model 2 was used to identify interaction sites between the receptor and ligand, several of which were subsequently tested using site-directed mutagenesis.…”
Section: Cdqo 41 59mentioning
confidence: 99%
“…The sequence alignment used to generate Model 2 is shown in Figure 3. As with previously published models (Bajorath et al, 1995a(Bajorath et al, , 1995bBajorath & Aruffo, 1997), we based the structural alignment of CD40 on CD40L on the crystal structure of TNF Receptor with TNF-p. Our assumption is that the high degree of structural similarity between CD40L and TNF-P (Karpusas et al, 1995) extends to the way that their receptors are structurally aligned. To align CD40L with CD40, our first step was to align the crystal structure of CD40L with the TNF-P/TNFR structure, using the strands A-H of TNF-J as structural equivalences (Karpusas et al, 1995).…”
Section: Cd4ol and Cd40 Structurementioning
confidence: 99%